2015
DOI: 10.1007/s10611-015-9591-5
|View full text |Cite
|
Sign up to set email alerts
|

Race, immigration, and homicide in contemporary Europe and the United States: an urban comparison

Abstract: In this paper we ask a key question: Do immigrants contribute a disproportionate amount of crime beyond what we would expect from native-born populations? We start with a description of the immigration and homicide literature in the United States and Europe and transition into a description of lessons learned from this topic in the United States. Specifically, we compare the level of immigration to white, black, and Latino homicide rates between 1985 and 2009. We compare and contrast racial/ ethnic/immigrant g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In any event, ethnic selectivity is less of a methodological concern here. Contrary to a significant part of the existing (quantitative) studies in the field of migration and crime (see for example [41,[45][46][47][48][49][50][51][52]) we do not compare immigrants with non-immigrants, nor are we primarily interested in understanding differences in crime among different ethnic minorities (we only use national origin as a control variable). There is nonetheless a possibility that the police focused more on unauthorized immigrants and asylum seekers in the procedure than on naturalized citizens and residence permit holders.…”
Section: Validitymentioning
confidence: 99%
“…In any event, ethnic selectivity is less of a methodological concern here. Contrary to a significant part of the existing (quantitative) studies in the field of migration and crime (see for example [41,[45][46][47][48][49][50][51][52]) we do not compare immigrants with non-immigrants, nor are we primarily interested in understanding differences in crime among different ethnic minorities (we only use national origin as a control variable). There is nonetheless a possibility that the police focused more on unauthorized immigrants and asylum seekers in the procedure than on naturalized citizens and residence permit holders.…”
Section: Validitymentioning
confidence: 99%
“…T. Lee and Martinez 2002; M. T. Lee et al 2001; Martinez, Iwama, and Stowell 2015; Martinez and Stowell 2012; Martinez et al 2010). These findings suggest support for the immigrant revitalization perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Yet in both Europe and in the United States, there remains a persistent linkage in media discourse between immigration and criminality (Schemer, 2014: 531), including sexual crime (Ticktin, 2008), and evidence shows that this stigmatization has consequences for public opinion and policy. As Martinez et al (2015) comment in the US context: ‘singling out immigrants for discrimination or punitive treatment will likely have a deleterious impact socially’ (p. 303). In Switzerland, a location culturally closer to our German case, in the context of campaigning in a referendum (2006) which resulted in further restrictions on immigration, researchers found that ‘repeated exposure to news depictions of asylum seekers as criminals and freeloaders resulted in more pronounced prejudicial attitudes at a later point in time’ (Schemer, 2014: 537).…”
Section: Introduction – the Cologne New Year’s Eve 2015–2016 Attacks ...mentioning
confidence: 99%
“…reduced negative attitudes (Schemer, 2014: 537). In other words, positive changes in media representation can impact public opinion and hence potentially arrest the downward spiral of a moral panic, in which public anxieties trigger punitive responses from the authorities which penalize and discriminate against immigrants, hence – given established links between stigmatization and deviancy – increasing the likelihood of their involvement in criminal activity (Cohen, 1972; Martinez et al, 2015).…”
Section: Introduction – the Cologne New Year’s Eve 2015–2016 Attacks ...mentioning
confidence: 99%